Pengaruh Penjualan, Biaya Operasional, Perputaran Kas, dan Perputaran Persediaan Terhadap Return On Investment (ROI) Pada Perusahaan Manufaktur (Studi Kasus Pada Perusahaan Food and Beverages yang Terdaftar di Bursa Efek Indonesia Periode 2013-2018) - Nita Prasetyawati; alean kistiani; milka susana (Universitas Boyolali, 2019)
Analysis of Return On Investment (ROI) is an analysis that is able to describe in detail the things that affect the efficiency and operation of the company. This study aims to determine whether there is the influence of sales, operating costs, cash turnover and inventory turnover on Return On Investment (ROI) in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2013 – 2018 period. and The factors that have the most significant effect on Return On Investment (ROI) in Manufacturing Companies listed on the Indonesian Stock Exchange for the 2013 – 2018 period. The population in this study is the financial data of manufacturing companies listed on Indonesia Stock Exchange (IDX) in 2013 – 2018. The sampling technique used was purposive sampling as many as 13 companies. The data analysis tool used in this study is multiple linear regression analysis, hypothesis testing and classical assumption analysis. Simultaneously there is a significant effect of sales (X₁), operating costs (X₂), cash turnover (X₃) and inventory turnover (X₄) to Return On Investment (Y), this is evidenced by the value of sig < 0,05. Partially inventory turnover (X₄) is the factor that has the most significant effect on Return On Investment (ROI) (Y), this is indicated by the sih-count value <0,05. Keyword : ROI, Sales, Costs, Cash Turnover, Inventory Turnover.